2022
DOI: 10.3390/cells11223566
|View full text |Cite
|
Sign up to set email alerts
|

Actin-Binding Proteins in Cardiac Hypertrophy

Abstract: The heart reacts to a large number of pathological stimuli through cardiac hypertrophy, which finally can lead to heart failure. However, the molecular mechanisms of cardiac hypertrophy remain elusive. Actin participates in the formation of highly differentiated myofibrils under the regulation of actin-binding proteins (ABPs), which provides a structural basis for the contractile function and morphological change in cardiomyocytes. Previous studies have shown that the functional abnormality of ABPs can contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 116 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that autophagy; actin-binding proteins, such as cofilin, Formin and capZ; and the MaPK/erK signaling pathway serve roles in cardiac hypertrophy (33)(34)(35). it has been reported that autophagosome formation depends on small GTPases (36).…”
Section: Genementioning
confidence: 99%
“…Previous studies have reported that autophagy; actin-binding proteins, such as cofilin, Formin and capZ; and the MaPK/erK signaling pathway serve roles in cardiac hypertrophy (33)(34)(35). it has been reported that autophagosome formation depends on small GTPases (36).…”
Section: Genementioning
confidence: 99%
“…increase the development of cardiac hypertrophy moreover its level is signi cantly increased in mammalian hypertrophic hearts(Kooij et al 2016). On the contrary Pan et al reported that in H9c2 cells the inhibition of pro lin-1 can attenuate cardiac hypertrophy(Pan et al 2022). …”
mentioning
confidence: 96%